Measuring Online Learning Strategies During The Covid-19 Pandemic: Instrument Validity and Reliability - Yanda, Diyan Permata; Ramadhanti, Dina (BAHASTRA, 2022)
This study aims to describe the validity and reliability of the learning strategy questionnaire instrument used during the Covid-19 pandemic. By using a quantitative approach, measurement of the learning strategy questionnaire was developed based on six language learning strategies, namely: cognitive strategies, memory strategies, compensation strategies, metacognitive strategies, affective strategies, and social strategies. A total of 17 students were randomly selected to be the test subjects of the learning strategy instrument. By using SPSS 23, the bivariate product moment correlate test was used to determine the validity of the questionnaire items and Cronbach's Alpha test to determine the reliability of the questionnaire. The results showed that as many as 124 questionnaire items were tested on respondents, it was found that 92 questionnaire items were declared valid and overall the questionnaire items were declared reliable or consistent. Thus, as many as 92 items of this learning strategy questionnaire statement can be used to measure the types of language learning strategies used by students, both for online learning and face-to-face learning.